Short Fatigue Crack Growth in a Residual Stress Field in a 7075 Al-Alloy after Shot Peening - Cerny, Ivo; Mikulova, Dagmar; Sis, Jiri (Communications - Scientific letters of the University of Zilina, 2012)
The paper contains results of an investigation of effects of shot peening on growth of physically short fatigue cracks in a 2.4 mm thick sheet of an aircraft V-95 Al-alloy (a type of a 7075 alloy), clad with a 7072 Al-alloy (Al-Zn1). Using an improved and verified experimental methodology, particularly direct current potential drop (DCPD) method, short fatigue cracks of the length from 0.2 mm to more than 3 mm, most of them between 0.8 – 1.5 mm, were prepared under high cycle fatigue repeated tensile loading of the constant nominal stress range 160 MPa, load asymmetry R 0. Edges of the specimens with already existing short fatigue cracks were then shot peened using two different groups of parameters. Some reference specimens without cracks were shot peened with the same parameters. Microhardness measurement and informative measurement of residual stresses near the peened edges were carried out. Significant retardation of crack growth was observed particularly in case of cracks shorter than 2 mm. The work was completed by a unique measurement of actual crack growth rate throughout the peened area with residual stresses starting with crack length less than 0.2 mm. Different stages of the growth are discussed.